Investigating the disinfecting efficacy of acetic and boric acid used by spraying on hatching goose eggs - Eroglu, M.; Erisir, Z.; Simsek, U. Gulcihan; Mutlu, S. Iflazoglu; Baykalir, Y.; Gungoren, A.; Bicer, Z. (Eugen Ulmer Gmbh Co, 2024)
This study was conducted to determine whether the disinfection of soiled goose eggs by spraying with tap water, acetic acid and boric acid solutions affects hatching performance and microbial load. A total of 1200 eggs were used for analysis of incubation characteristics and a total of 30 eggs were used for microbiological analysis. The study consisted of five treatment groups: clean eggs (PC, positive control); dirty eggs (NC, negative control); eggs sprayed with tap water (TW); eggs sprayed with 3% acetic acid solution (A3); eggs sprayed with 3% boric acid solution (B3). The differences between the groups for hatching from set eggs, hatching from fertile eggs, embryonic mortality rate, and non-commercial gosling rate were not statistically significant. In terms of microbial load, differences between the groups were statistically significant for total mesophilic aerobic bacteria (P < 0.001), total coliforms (P < 0.000), Enterobacteriaceae (P < 0.01), and Escherichia coli ( P< 0.05). The most effective treatment group for total mesophilic aerobic bacteria was B3, which reduced the number of colonies on the shell by 2.93 log10 cfu; for Enterobacteriaceae , it was TW, which reduced the number of colonies by 1.79 log10 cfu; for coliforms, it was TW and A3, which reduced the number of colonies by 1.87 log10 cfu. This study showed that spraying with tap water, acetic acid, and boric acid solutions successfully reduced the microbial load on contaminated goose eggs and did not negatively affect the incubation characteristics.
Untersuchung der Desinfektionswirkung von Essig-und Borsäure durch Besprühen von Gänsebruteiern
Keywords: acetic asid; boric acid; disinfection; geese; microbial load; spraying